Lymphaticovenular Anastomosis for Patients with Lymphedema of the Lower Extremity: A Cumulative Experience at Siriraj Hospital - Yodrabum N. (2023)
Background: Lower extremity lymphedema is a chronic disturbing condition that commonly results from cancer or cancer treatment. Lymphaticovenular anastomosis (LVA) is one of the most effective lymphedema operations. Over eight years of data collection, almost a hundred lower extremity lymphedema patients underwent LVA operations at Siriraj Hospital. Objective: To summarize the attributes of lower extremity lymphedema patients treated by the LVA operation at Siriraj Hospital, and to assess their surgical treatment outcomes. Materials and Methods: The present study employed a single-center retrospective review to evaluate the characteristics and outcomes of lower extremity lymphedema patients that underwent LVA operations between 2010 and 2018 at Siriraj Hospital. The reduction of limb circumference and the cellulitis rate was intended to measure the LVA operation's effectiveness by using descriptive (SPSS) statistics. Results: Ninety-four lower extremity lymphedema patients underwent the LVA operation. The average number of anastomosis was 2.9±1.2. The post-operative circumferential reductions were 4.3±1.8 cm (84.3%) at 10 cm above the patella and 5.3±0.9 cm (89.8%) at 10 cm below the tibial tuberosity. Episodes of cellulitis were consistently decreased from 1.9±0.3 to 0.6±0.1 times per year. Among the non-surgical treatments, 69.1% of the lymphedema patients were treated with pressure garments. However, only 6.4% of those patients applied skincare. Conclusion: LVA is an effective operation for lower extremity lymphedema. LVA can satisfactorily reduce excessive lymphedematous tissues and cellulitis episodes. According to the cumulative data of LVA at Siriraj Hospital, the outcome of LVA in the lower extremity has an acceptable outcome. The same holds true for the upper extremity. Unfortunately, some patients disregarded the surgical treatment. There should be an effective healthcare team to encourage this valuable treatment practice.